The Role of Knowledge Management Mediation in The Relationship Between Risk-Taking and Proactiveness on Employee Performance in the Banking Sector - Luther Aprinando Pentury; Andreas Wahyu Gunawan (Jurnal Economic Resource, 2026)
This study aims to analyze the influence of risk-taking, proactiveness, and knowledge management on employee performance in the Indonesian banking sector. The rapid dynamics of the banking industry and high demands for innovation underscore adaptive capabilities and knowledge management as key success factors. Employee performance, as a core organizational asset, is significantly affected by how individuals and organizations respond to change and leverage existing knowledge. This research employs a quantitative, survey-based approach. Data were collected through questionnaires distributed to banking employees in Indonesia. The research sample was drawn using a purposive sampling technique with specific criteria. The collected data were then analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with SmartPLS software. The findings indicate that both risk-taking and proactiveness have a positive and significant influence on knowledge management. This suggests that a higher propensity for employees to take calculated risks and demonstrate proactivity leads to more effective knowledge management processes in the workplace. Furthermore, risk-taking and knowledge management were found to have a positive and significant influence on employee performance. Interestingly, proactiveness did not show a direct significant influence on employee performance; however, its influence was fully mediated by knowledge management. This finding underscores the crucial mediating role of knowledge management in linking proactiveness to improved performance. The managerial implications of this study highlight the importance of banking institutions to foster a culture that supports measured risk-taking and proactive initiatives among employees. Moreover, investing in effective knowledge management systems and processes is vital to convert proactiveness into tangible performance improvements. This research contributes to the literature on the determinants of employee performance in the banking industry, particularly in the context of the strategic role of knowledge management in developing countries like Indonesia.